An HST Optical to Near-IR Transmission Spectrum of the Hot Jupiter WASP-19b: Detection of Atmospheric Water and Likely Absence of TiO - Huitson, C; Sing, D; Pont, F; Fortney, J; Burrows, A; Wilson, P; Ballester, G; Nikolov, N; Gibson, N; Deming, D; Aigrain, S; Evans, T; et al. (2013)
We measure the transmission spectrum of WASP-19b from 3 transits using low-resolution optical spectroscopy from the HST Space Telescope Imaging Spectrograph (STIS). The STIS spectra cover a wavelength range of 0.29-1.03 microns with resolving power R=500. The optical data are combined with archival near-IR data from the HST Wide Field Camera 3 (WFC3) G141 grism, covering the wavelength range 1.087-1.687 micron, with resolving power R=130. We obtain the transmission spectrum from 0.53-1.687 microns with S/N levels between 3000 and 11,000 in 0.1 micron bins. WASP-19 is a very active star, with optical stellar flux varying by a few per cent over time. We correct the transit light curves for the effects of stellar activity using ground-based activity monitoring with the Cerro Tololo Inter-American Observatory (CTIO). While we were not able to construct a transmission spectrum using the blue optical data due to the presence of large occulted star spots, we were able to use the spot crossings to help constrain the mean stellar spot temperature. To search for predicted features in the hot-Jupiter atmosphere, we also define spectral indices for differential radius measurements to specifically search for the presence of TiO and alkali line features. Our measurements rule out TiO features predicted for a planet of WASP-19b's equilibrium temperature (2050 K) in the transmission spectrum at the 2.7-2.9 sigma confidence level, depending on atmospheric model formalism. The WFC3 transmission spectrum shows strong absorption features due to the presence of H2O, which is detected at the 4 sigma confidence level between 1.1 and 1.4 microns. The results indicate that WASP-19b is a planet with no or low levels of TiO and without a high C/O ratio. The lack of observable TiO features are possibly due to rainout, breakdown from stellar activity or the presence of other absorbers in the optical.